Failure to recover from proactive semantic interference and abnormal limbic connectivity in asymptomatic, middle-aged offspring of patients with late-onset Alzheimer’s disease - Sánchez, Stella M. (2017)
Fil: Sánchez, Stella M. Fundación para la Lucha contra las Enfermedades Neurológicas de la Infancia. Servicio de Psiquiatría; Argentina